PENGARUH IKLIM KERJA DAN DUKUNGAN ATASAN TERHADAP KINERJA PEGAWAI DINAS KESEHATAN KABUPATEN PATI DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL MEDIASI ( STUDI PADA DINAS KESEHATAN KABUPATEN PATI) - Rachmawati, Heny (Students Journal of Economic and Management, 2012)
Officer performance asÂ government Officer is good job(activity result and having responsibility in quality and also amount by officer according to fundamental duty and function given to the. And officer performance will prosper if stays at work environment having good climate and Condusive. Superior support from can become strength to increase successfulness of employee in an organization. Interrelationship of employee to organization of its(the place works recognized as commitment term of organization. Organizational commitment required as one of employee performance indicator. Employee with hopeable high commitment will show optimal performance. Extract Sub-Province Public Health Service in execution of autonomâs area aimed at improvement of officer performance so that in attainment of vision and mission earns efficient and is better. For the purpose writer tries checks the relation of job activity climate and Superior support to employee performance Pati District Health Office with organizational commitment as mediatet variable. This research executed in Extract Sub-Province Public Health Service with population were 109 people, Research type is Explanatory Research, Research variable is free variable that is activity climate Â and Superior supportÂ while variable tied is organizational commitment, Employee Performance. Data type applied by secondary data and primary data through questionaire gathering. Technics of analysis applied applies validity test, reliability test , doubled linear regression and test mediasi path analysis the relation of between variable. Result of research indicates that variable job(activity climate and Superior supportÂ Â influential positive and signifikan to organizational commitment, variable job(activity climate, organizational superior support from and commitment had an effect on positive and signifikan to Â employee performance. While Commitment of Organizational signifikan mediation variable job(activity climate doesnt superior support from and to employee performance. Keyword :Â Â Â Â Â Â Â Â Â Â Â Â Job(activity Climate, Superior Support From, Organizational Commitment and Officer performance